1984
DOI: 10.1146/annurev.ph.46.030184.002155
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatocytes in Monolayer Culture: A Model for Studies on Lipoprotein Metabolism

Abstract: Primary hepatocyte cultures are ideal models in which to investigate regulation of lipoprotein synthesis and catabolism by the liver. Not only can one regulate the physiological and nutritional state of the donor animal, but one can also manipulate the culture milieu. A possible problem that arises in prolonged incubations is the accumulation of metabolites in the culture media, which may alter the function of the cells. Studies using more novel culturing techniques such as "perifusion" may resolve this techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The reasons for discrepancies in response to fatty acid among the various studies with intact perfused livers or using isolated hepatocytes in tissue culture are not understood at present. As stated by Forte [37], however, conditions must be defined carefully if tissueculture experiments are to be compared properly in evaluation of regulation of apolipoprotein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for discrepancies in response to fatty acid among the various studies with intact perfused livers or using isolated hepatocytes in tissue culture are not understood at present. As stated by Forte [37], however, conditions must be defined carefully if tissueculture experiments are to be compared properly in evaluation of regulation of apolipoprotein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including our own, revealed that adult rat hepatocytes in primary culture retained numerous liver-specific functions and responded to various hormones. 14) This fact encouraged us to identify as-yet-unknown hepatotrophic factor(s) via the establishment of an in vitro assay of DNA synthesis in adult rat hepatocytes. In this section, we describe the previous efforts leading to purification and cDNA cloning of HGF.…”
Section: Discovery Of Hgf As a Hepatotrophic Factormentioning
confidence: 99%
“…Early reports concluded that they represented ideal models to investigate regulation of lipoprotein synthesis and catabolism (62). Hepatocytes form fatty acids from carbohydrates and synthesize triglycerides from fatty acids and glycerol.…”
Section: Expression and Regulation Of Liver Functionsmentioning
confidence: 99%